Evaluation of Aerosol Contamination during Ultrasonic Procedures - Verma, Neha; Baidya, Dhritiman; Makhijani, Barkha; Shetty, Neema; Mathur, Aditi; Manohar, Balaji (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Operator safety during dental & periodontal treatment is a non-negotiable necessity. The production of airborne material, during dental procedures is obvious to the dentist, dental team and the patient. Aim: The aim of the present study was to evaluate, the colony forming units (CFU) generated from aerosol during ultrasonic procedure in gingivitis and periodontitis subjects that act as a potential risk factor for spread of infectious agents for both operator and patients. Materials and Methods: The present study included 18 subjects which were randomly assigned into 3 equal groups. Group I (Control group) subjects were treated with ultrasonic scaling alone, whereas; Groups II & Group III (Test groups) subjects used pre-procedural mouth-rinses before scaling & root planing (Chlorhexidine and Povidone Iodine). Blood agar plates were used to assess the aerosol contamination and were placed at operator’s eye level, subject’s eye & chest level. These plates were then incubated for 72 hours and microbial growth were quantified as colony forming units (CFU/plate). Different colonies were identified by standard biochemical methods. Results: This study showed that the antiseptic mouth-rinses significantly reduce the bacterial CFU in the aerosol. Povidone Iodine was found to be superior to Chlorhexidine when used pre-procedurally. Conclusion: The following conclusion was drawn that the use of pre-procedural rinses significantly reduced the aerosol contamination and hence chances of cross-infection in the dental units.